Synthesis, Characterization and Preliminary Screening of New N-Substituted -8-Methyl-4-Hydroxy-2-Quinolone -3-Carboxamides as Potential Anticancer Agents - Altaher, Dania; Zalloum, Hiba; Sweidan, Kamal; Sabbah, Dima A.; AlSalamat, Husam; Sunjuk, Mahmoud; Isleem, Reem (Current Organic Synthesis, 2025)
IntroductionA new series of 4-hydroxy-8-methyl-2-oxo-1,2-dihydroquinoline-3-carboxamide derivatives has been synthesized in good yields, followed by complete characterization using 1D-NMR, 2D-NMR, and IR techniques.MethodsThe final products contain amide, hydroxyl, and aromatic functional groups that usually show significant bioactivity. The target products have been examined towards three cancer cell lines, namely colorectal cancer cell line (HCT116), breast cancer cell line (MCF-7), and leukemia cell line (K562) in addition to the fibroblast cells, that were used as a model for normal human tissue.ResultsThe anticancer results signified that compound 6 showed the most activity in the series accomplished with IC50 values of 14.6, 5.3 and 12.8 M,ConclusionOther compounds exhibited considerable activity, such as compounds 9 (IC50 3.5 and 19.0 M), 10 (IC50 12.6 M), and 11 (IC50 10.3 M) against the three cancer cell lines HCT116, MCF-7 and K562, respectively.
Keywords: K562